Proceedings of the Fourth Workshop on Computational Linguistics And Clinical Psychology –- From Linguistic Signal to 2017
DOI: 10.18653/v1/w17-3107
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Anxiety through Reddit

Abstract: Previous investigations into detecting mental illnesses through social media have predominately focused on detecting depression through Twitter corpora (De Choudhury et al., 2013;Resnik et al., 2015;Pedersen, 2015). In this paper, we study anxiety disorders through personal narratives collected through the popular social media website, Reddit. We build a substantial data set of typical and anxietyrelated posts, and we apply N -gram language modeling, vector embeddings, topic analysis, and emotional norms to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(122 citation statements)
references
References 14 publications
2
117
0
3
Order By: Relevance
“…Dunlop et al [10] show that online discussion forums were associated with increases in suicidal ideation while Luxton et al [19] show that social media can pose a threat to some vulnerable groups of society. Some uni-modal studies [21,27] have examined behavioral markers of depression in social media by leveraging the posts on Reddit and Twitter.…”
Section: Related Workmentioning
confidence: 99%
“…Dunlop et al [10] show that online discussion forums were associated with increases in suicidal ideation while Luxton et al [19] show that social media can pose a threat to some vulnerable groups of society. Some uni-modal studies [21,27] have examined behavioral markers of depression in social media by leveraging the posts on Reddit and Twitter.…”
Section: Related Workmentioning
confidence: 99%
“…Wallace et al (2014) tackled irony detection and concluded that Reddit provides a lot of context, which can help in dealing with the ambiguous cases. Shen and Rudzicz (2017) achieved good results in anxiety classification using the Linguistic Inquiry and Word Count (LIWC) dictionary (Pennebaker et al, 2003), n-grams, and topic modeling. To the best of our knowledge, ours it the first work on using Reddit as a source of data for personality prediction.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Wallace et al (2014) tackled irony detection and concluded that Reddit provides a lot of context, which can help in dealing with the ambiguous cases. Shen and Rudzicz (2017) achieved good results in anxiety classification using the Linguistic Inquiry and Word Count (LIWC) dictionary , n-grams, and topic modeling. To the best of our knowledge, ours it the first work on using Reddit as a source of data for personality prediction.…”
Section: Background and Related Workmentioning
confidence: 99%